Social Determinants of Maternal Health and Birth Outcomes. Issue 1 (January 2017) - N/A,
Abstract : Social determinants of health such as racial discrimination, poor quality neighborhoods, and acculturation may increase risk of negative mental health and birth outcomes for minority women in the United States. Nurses can take leadership roles in creating policies that promote economic development, reduce poverty, reduce residential segregation, promote healthier neighborhoods, and support immigrant women.